Pendampingan Guru Madrasah di Kota Serang dalam Pembuatan Alat Praktikum Fisika Berbasis Higher Order Thinking Skills (HOTS) - Asep Saefullah; Yuvita Oktarisa; Muhammad Fatkhurrokhman; Lukman Nulhakim; Diana Ayu Rostikawati (Fakultas Teknik, Universitas Bangka Belitung, 2021)
Madrasah is one of the formal educational institutions that aims to develop the potential of students to the maximum. The skills acquired by students are expected to be sufficient provisions for students to be able to compete globally, but still pay attention to local wisdom. Madrasah teachers must be able to equip themselves to be able to become reliable facilitators, so that they can lead students to the gates of independence. Madrasah teachers must equip students to have Higher Order Thinking Skills (HOTS). HOTS can equip madrasah students to have the ability to think critically, negatively, logically and systematically. Practicum activity is one of the lessons that can be done so that students have HOTS. However, madrasah teachers are often confronted with the inadequacy of the school's physics practicum tools. Through this community service activity, teachers receive assistance on how to make physics practicum tools and their guidelines. In addition, teachers also receive assistance on how to manage learning that can train HOTS. The results of community service show that madrasah teachers are able to make physics practicum tools that can be used in HOTS-based learning.